Hydrodynamics of dual circulating fluidized bed reactor for chemical looping combustion. (November 2020) - Uraisakul, Watchara; Chalermsinsuwan, Benjapon; Piumsomboon, Pornpote
Abstract: Carbon dioxide (CO2 ) has been increasingly released to the environment with the increased electricity demand via fossil fuel combustion. The alternative solution is the combustion unit that prevents CO2 from releasing. Chemical looping combustion is the combustion unit that can achieve this objective and provides high purity of a CO2 product for meaningful uses. The high efficiency of the process is achieved by designing good reactor hydrodynamics. A dual circulating fluidized bed reactor was then investigated in this study. The two parameters were studied; the temperature of the reactor (A) and the ratio of coal velocity to the weight of oxygen carrier (B). The two responses were analyzed; 1) combustible gas percentage from a fuel reactor, and 2) CO2 percentage from an air reactor. The 3 k factorial experimental was used for systematic experimental design which included the curvature behavior of the result. The results indicated that parameters A and B affected the combustible gas percentage from the fuel reactor. However, only B affected the CO2 percentage from the air reactor. The high A and B gave a high combustible gas percentage from the fuel reactor and high CO2 percentage from the air reactor. The high combustible gas percentage from the fuel reactor indicated the incomplete combustion and the high CO2 percentage from the air reactor indicated the high CO2 releasing to the environment. The low values of A and B then supported the proper hydrodynamics in these reactors which will provide the efficiency of fuel usage, the reduction of CO2 emission to the environment, and the mitigation of the environmental crisis.